The global health and economic impact of low-back pain attributable to occupational ergonomic factors in the working-age population by age, sex, geography in 2019 - Chen, Ningjing; Fong, Daniel Yee Tak; Wong, Janet Yuen Ha (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVE ': 'Occupational ergonomic factors (OEF) include physical exertion, demanding posture, repetitive work, hand-arm vibration, kneeling or squatting, rising, and climbing, which are risk factors for low-back pain (LBP). This study aimed to examine the prevalence, years lived with disability (YLD), healthcare costs, and productivity losses of LBP attributable to OEF by age, sex, World Health Organization region, and country in 2019. ' ' METHODS ': 'In this cross-sectional study, prevalence and YLD were extracted from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019. Employment statistics were obtained from the International Labor Organization websites. Health and economic impact was estimated for 192 countries and territories using the population attributable fraction method. ' ' RESULTS ': 'Globally, OEF were responsible for 126.1 million prevalent cases of LBP and 15.1 million YLD in the working-age population (aged 15–84 years) in 2019, with the Western Pacific region suffering most. OEF-attributable LBP led to 216.1 billion of economic losses worldwide. Of these, 47.0 billion were paid in healthcare costs, with the public sector serving as the largest contributor (59.2%). High-income countries bore >70% of global economic burden, whereas middle-income countries experienced >70% of global YLD. Generally, more prevalent cases and healthcare costs were found among females, whereas more YLD, productivity losses, and total costs were found among males. ' ' CONCLUSIONS ': 'Globally, OEF-attributable LBP presented a heavy burden on health and economic systems. Exercise together with education, active monitoring, evidence-based medical practices, alternative cost-effective solutions, and prioritizing health policies are needed.
Keywords: back pain; economic impact; ergonomic factor; healthcare cost; low-back pain; occupational ergonomic factor; productivity loss; years lived with disability